AVICENNA JAGAKARSA SCHOOL TEACHERS 'READINESS IN IMPLEMENTING E-LEARNING IN PANDEMIC COVIDES 19 - Kristiningsih Kristiningsih (SAP (Susunan Artikel Pendidikan), 2020)
AbstractThe Covid-19 pandemic has resulted in fundamental policy changes in the world of education in the country. The Indonesian Minister of Education and Culture, Nadiem Anwar Makarim has issued a number of policies to regulate spending activities during this pandemic. This was issued through Circular No. 4 of 2020, which is about the Implementation of Education Policy in the Emergency Spread of Coronavirus Disease (Covid-19), dated March 24, 2020. The most basic policy is to change the way of teaching and learning of students and teachers with learning policies from home with online learning (e-learning). Many schools want to implement e-learning. However, every school that wants to implement e-learning needs to pay attention to its level of readiness both in terms of infrastructure and in the technical capabilities of its users. The e-learning readiness is known as e-learning readiness. E-learning readiness is not limited to preparation before implementation, but can also be done for organizations that have implemented e-learning. This study aims to determine the level of readiness of the Avicenna Jagakarsa School in the application of e-learning and what factors are still weak and need to be improved in the application of e-learning. Method This study uses a questionnaire based on Aydin & Tasci's e-learning readiness (ELR) model with its rating scale grouped into four factors. These factors are human, self-development, technology, and innovation. The results showed that Avicenna Jagakarsa School Teacher had an e-learning readiness index overall ELR score = 4.31. This shows that the Avicenna Jagakarsa School is included in the category of ready to implement e-learning but still needs a little improvement.Keywords: e-learning, e-learningreadines, ELR, co-19